Explaining differences in the frequency of lung cancer detection between the National Lung Screening Trial and community-based screening in Manchester, UK. (September 2022) - Robbins, Hilary A.; Zahed, Hana; Lebrett, Mikey B.; Balata, Haval; Johansson, Mattias; Sharman, Anna; Evans, D. Gareth; Crosbie, Emma J.; Booton, Richard; Landy, Rebecca; Crosbie, Philip A.J.
Highlights: Nearly 3-fold higher lung cancer detection was observed in the community-based Manchester Lung Health Checks versus the US National Lung Screening Trial. This difference was partially attributable to differences in eligibility criteria and baseline lung cancer risk distributions. The remaining 60% increase in Manchester may related to increased detection among people with older age, living in areas of high socioeconomic disadvantage, and with obstructive lung disease. Abstract: Background: The frequency of lung cancer detection in the Manchester Lung Health Checks (MLHCs), a community-based screening service, was higher than in the National Lung Screening Trial (NLST) over two screening rounds. We aimed to identify the potential reasons for this difference. Methods: We analyzed individual-level data from NLST and MLHCs, restricting to MLHCs participants who met NLST eligibility criteria. We calculated 'detection ratios' comparing the frequency of lung cancer detection in MLHCs vs NLST, first after excluding NLST participants ineligible by MLHC eligibility criteria (6-year lung cancer risk ≥ 1.51 %), and then after standardization to remove the influence of different distributions of baseline lung cancer risk. Results: Among the 1, 079 MLHCs participants who met NLST eligibility criteria, 4.7% were diagnosed with lung cancer over two screening rounds compared with 1.7% in NLST, giving an initial detection ratio of 2.6 (95%CI 2.2–3.0). This was reduced to 2.2 (95%CI 1.3–2.3) after imposing the MLHCs eligibility criterion on NLST, and further to 1.6 (95%CI 1.2–2.1) after removing the influence of different risk distributions. In stratified analyses, the standardized detection ratio was particularly elevated in individuals who were older, living in areas of high socioeconomic disadvantage, or had an FEV/FVC ratio less than 60. Conclusions: The 2.6-fold higher lung cancer detection in the community-based MLHCs vs NLST is partly explained by differences in eligibility criteria and baseline risk distributions. The residual 60% increase may relate to higher detection in certain risk groups, including older participants, those with more obstructive lung disease, and those living in areas of socioeconomic disadvantage.